For a function to be even, it has to meet this condition:
![f(x)=f(-x)](https://img.qammunity.org/2023/formulas/mathematics/high-school/d5txlwfgs1sgi42dr82a0kuoncotldq3mc.png)
To check if the given is an even function, find f(x) and f(-x) and see if they are equal:
![\begin{gathered} f(x)=5-3x \\ f(-x)=5-3(-x)=5+3x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/y6fma385ogulwudh0qamtwk4rif3komvzj.png)
In this case, the function is not even.
For a function to be odd, it has to meet this condition:
![f(-x)=-f(x)](https://img.qammunity.org/2023/formulas/mathematics/high-school/2e7atz772vwog13fsb2sz63eyu41ii9qrs.png)
We already know that f(-x)=5+3x. Let's find -f(x):
![\begin{gathered} f(x)=5-3x \\ -f(x)=-5+3x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wjbnsambw0h1a64axk1dqy0ythqbhotg7v.png)
According to this -f(x) is not equal to f(-x), which means that the function is not odd neither.
The answer is that the function is not even nor odd.